2016
DOI: 10.2147/ijn.s93483
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the NF-κB pathway in macrophages using mannosylated, siRNA-delivering nanoparticles can induce immunostimulatory and tumor cytotoxic functions

Abstract: Tumor-associated macrophages (TAMs) are critically important in the context of solid tumor progression. Counterintuitively, these host immune cells can often support tumor cells along the path from primary tumor to metastatic colonization and growth. Thus, the ability to transform protumor TAMs into antitumor, immune-reactive macrophages would have significant therapeutic potential. However, in order to achieve these effects, two major hurdles would need to be overcome: development of a methodology to specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…vaccination (Figure 6 ). In addition to our data, previous study showed that mannosylated polymer nanoparticles specifically and effectively delivered siRNA to tumor associated macrophages (TAMs) (Ortega et al, 2015 ) and made the encapsulated siRNA more capable to manipulate NF-κB signaling in the tumor (Ortega et al, 2016 ); and man-chitosan nanoparticles effectively enhanced the transfection efficiency of DNA and lowered the toxicity of chitosan in peritoneal macrophages (Hashimoto et al, 2006 ). Taken together, we and others demonstrate that mannosylation of drugs, proteins, genes or their delivery vectors significantly enhance their accessibility to and transfection efficiency in the macrophages, therefore may greatly enhance the therapeutic efficiency or vaccine immunogenicity.…”
Section: Discussionsupporting
confidence: 74%
“…vaccination (Figure 6 ). In addition to our data, previous study showed that mannosylated polymer nanoparticles specifically and effectively delivered siRNA to tumor associated macrophages (TAMs) (Ortega et al, 2015 ) and made the encapsulated siRNA more capable to manipulate NF-κB signaling in the tumor (Ortega et al, 2016 ); and man-chitosan nanoparticles effectively enhanced the transfection efficiency of DNA and lowered the toxicity of chitosan in peritoneal macrophages (Hashimoto et al, 2006 ). Taken together, we and others demonstrate that mannosylation of drugs, proteins, genes or their delivery vectors significantly enhance their accessibility to and transfection efficiency in the macrophages, therefore may greatly enhance the therapeutic efficiency or vaccine immunogenicity.…”
Section: Discussionsupporting
confidence: 74%
“…We and others have shown that metabolic reprogramming and resulting substrate preference in response to activating stimuli play pivotal roles in immune cell biology, acting as a determinant of inflammatory potential in MFs and dictating functionality of NK, T, and B cells (9, 11-13, 19, 54, 66, 68-72). Based on the importance of metabolism in determining immunophenotype and response, nutrient transporters may be excellent targets to regulate MF activation and subtypes, allowing these immune cells to be successfully targeted through approaches such as nanoparticle delivery (73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 99%
“…Ortega et al ( 2015 ) reported that mannosylated polymer nanoparticles were able to deliver siRNA to TAMs in vitro and in vivo in the peritoneum of ovarian tumor bearing mice and in TAMs present in lung metastases. In addition, delivery of siRNA targeting the NF-κB pathway into TAMs of tumor bearing mice resulted in induction of a proinflammatory immunogenic phenotype in transfected macrophages and yielded an antitumor phenotype (Ortega et al 2016 ). Moreover, dual targeted immunotherapy via in vivo delivery of biohybrid siRNA-peptide nanoparticles to tumor macrophages substantially reduced the recruitment of TAMs in lung tumor tissue, reduced tumor size, and increased animal survival (Conde et al 2015 ).…”
Section: Transformation Of Tams Into M1 Proinflammatory Macrophagesmentioning
confidence: 99%